PEMBELAJARAN MENULIS TEKS PERCAKAPAN DALAM BAHASA MAKASSAR MENGGUNAKAN MEDIA GAMBAR SISWA KELAS X SMA NEGERI 6 KABUPATEN JENEPONTO - Basyati, Nisa Nurhikmah; Daeng, Kembong; Yunus, Andi Fatimah (Journal Studies in Indonesian Language and Literature, 2024)
This study aims to describe the skills of writing conversational texts using image media in class X students of SMA Negeri 6 Jenepnto Regency. This research is a quantitative descriptive research design. The population of this research is the design of this study, namely all students of class X SMA Negeri 6 Jeneponto Regency totaling 360 people which are divided into 10 classes. The samples in this study were representatives of class X, namely class X Mipa 3 students of SMA Negeri 6 Jeneponto Regency, totaling 36 students. The sampling used in this study is a random sampling technique. The technique used to collect data in this research is a test technique. The results showed that the tenth grade students of SMA Negeri 6 Jeneponto Regency had not achieved the planned achievement standard of 75% with minimum completeness criteria (75 KKM). Based on the criteria for assessing the overall ability level of students is at a good level . this can be seen from the results of the assessment, it turns out that students who get the minimum completeness criteria (KKM) are 20 students with a percentage of 55.5% and those who get a score below the KKM are 16 students with a percentage of 44.5%. In accordance with the results of this study, it was suggested that learning local languages ​​should continue to be held because it is one of Indonesia's cultural treasures that must be preserved and preserved. In addition, regional language learning is given more attention and explained in more detail so that students understand better, especially learning about writing in the Makassar language.